Clinical characteristics and healthcare utilization of patients with multicentric Castleman disease. (11th September 2014) - Casper, Corey; Teltsch, Dana Y.; Robinson, Don; Desrosiers, Marie‐Pierre; Rotella, Philip; Dispenzieri, Angela; Qi, Ming; Habermann, Thomas; Reynolds, Matthew W.
Summary Multicentric Castleman disease (MCD) is a rare lymphoproliferative disease. Little is known about how patient clinical features and healthcare utilization varies by human immunodeficiency virus (HIV) status and disease subtype. Data of MCD patients identified between 2000 and 2009 were collected from medical records at two United States treatment centres. Clinical, demographic, and biochemical characteristics, drug therapies and medical utilization were descriptively reported by HIV status and cell histology, and statistically compared with the Fisher's Exact and Kruskal–Wallis tests. Patients (n = 59) had a pathologically and clinically confirmed MCD diagnosis: plasmacytic (42%), hyaline vascular (29%) and mixed (15%); 10% had HIV infection. In the first year after diagnosis, MCD patients on average saw a healthcare provider more than six times, were hospitalized at least once and underwent frequent radiological and laboratory testing. Rituximab was the most commonly used drug therapy, followed by corticosteroids and conventional chemotherapy. One‐ and 2‐year survival was excellent in HIV‐negative patients (100% and 97%, respectively) but inferior for HIV‐positive cases (67% and 67%, respectively). Heterogeneous treatment decisions were observed in this MCD study; HIV status was the only distinguishing clinical criteria associated with pharmacotherapies. Additional research is necessary to guide treatment of this rare lymphoproliferative disorder.